ADVERSE DRUG REACTION PROFILE OF ANTI-SNAKE VENOM IN A TERTIARY CARE HOSPITAL - Dr. Ayyappan J; Dr. Nalini GK; MS, Dr. Bharath; K, Dr. Vishnu; Dr. Nagesh HN; Dr. Nishitha SB (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Snake envenomation is a major public health issue, particularly in tropical regions like India, where an estimated 250,000 snake bite cases occur annually. The administration of anti-snake venom (ASV) is the primary treatment modality; however, adverse drug reactions (ADRs) associated with ASV pose a significant clinical challenge. This retrospective study aims to evaluate the incidence, severity, and clinical outcomes of ASV-related ADRs in patients treated at a tertiary care hospital. A total of 150 cases from June 2022 to May 2024 were analyzed, documenting demographic distribution, reaction profiles, severity classifications, and management strategies. Results: Among 150 patients, vascular toxic snakebites were the most common. The 21–30 years age group was predominantly affected, with a male preponderance. ASV-related adverse reactions occurred in 60% (n=90) of cases, with itching (56.7%) being the most frequently reported symptom. Other reactions included chills and rigor (30%), nausea and vomiting (12.2%), and severe respiratory distress (1.1%) requiring intubation. The 20-minute Whole Blood Clotting Test (WBCT) was abnormal in 43.3% of patients. Intradermal ASV sensitivity testing was performed in 54.7% of cases. The majority of patients experienced mild envenomation, with an average hospital stay of 3 days. Recovery was achieved in 81.3%, while 18.7% were referred to higher centers. Conclusion: This study highlights the high incidence of ASV-related adverse reactions, emphasizing the need for careful monitoring and pre-medication strategies to mitigate risks.